2010
DOI: 10.1007/s00134-010-1951-0
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant and postpartum admissions to the intensive care unit: a systematic review

Abstract: ICU admission of pregnant and postpartum women occurs infrequently, with obstetric conditions responsible for the majority of ICU admissions. The ICU admission profile of women was similar in developed and developing countries; however, the maternal mortality rate remains higher for ICUs in developing countries, supporting the need for ongoing service delivery improvements. More studies are required to determine the impact of ICU admission for pregnant and postpartum women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
222
8
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(273 citation statements)
references
References 44 publications
32
222
8
11
Order By: Relevance
“…Pregnancy-related ICU admission rates in developed countries have been reported to be less than 2%, whereas those in developing countries have been reported to be more than 10% of the total deliveries (1,3,7,(15)(16)(17)(18) (2). The differences in admission rates might be related to the change in ICU admission criteria over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy-related ICU admission rates in developed countries have been reported to be less than 2%, whereas those in developing countries have been reported to be more than 10% of the total deliveries (1,3,7,(15)(16)(17)(18) (2). The differences in admission rates might be related to the change in ICU admission criteria over time.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, obstetric complications requiring admission to the ICU include hypertension, obstetric haemorrhage, severe pre-eclampsia/eclampsia, obstructed labour, puerperal sepsis and unsafe abortion (1,3,6,7,15,22,23). A study in a regional hospital in Hong Kong on 50 obstetric patients reported postpartum haemorrhage, pregnancy-associated hypertension and sepsis as the main causes of obstetric admission to Turk J Anaesthesiol Reanim 2017; 45: 303-9 (24).…”
Section: Discussionmentioning
confidence: 99%
“…8 With 76% antenatal patients, this is in correlation with a study showing that the ICU admission profile of women was similar in developed and developing countries. 9 As per the causes, both obstetric and non-obstetric, seeking ICU care, it shows that there is no change in common cause of ICU admissions over a last decade. 10 Among early pregnancy complication group, abortion-related hospital admissions predominated.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de la implementación de medidas como los cambios en las técnicas de asepsia, el uso de antibióticos de amplio espectro, la institucionalización del parto y el aná-lisis de los casos de muertes maternas dentro de los procesos de vigilancia epidemiológica, la sepsis materna continúa como una de las primeras cinco causas de muerte materna (MM) en el mundo (2,3). En Estados Unidos, para el periodo 2011-2013, el reporte de mortalidad relacionada con el embarazo señala a la sepsis como la tercera causa de muerte materna, con el 12,7 % de las muertes (4) y un 15 % de los ingresos de mujeres gestantes a unidades de cuidado intensivo (UCI) (5). Las MM por sepsis son más frecuentes en África, Asia, América Latina y el Caribe que en los países desarrollados (3).…”
Section: Introductionunclassified